The Urgency of Regulations for the Exercise of Copyright as a Fiduciary Collateral - Nurul Fazri Elfikri; Andrew Shandy Utama; Mutiah Primadya (LEGAL BRIEF, 2022)
expanded its use as an object of guarantee to obtain credit or financing from financial institutions. The problem faced in Indonesia is that there need to be supporting devices in implementing the regulations in article 16 paragraph (3), such as the procedures for implementing it, assessing the economic value of Copyright, and how to disburse from Copyright. The research method used in the framework of this research is the normative legal research method. Although Copyright can be used as collateral as stipulated in law No. 28 of 2014, It still needs to be implemented in its practice. Copyright has economic value and can be transferred either in whole or part due to inheritance, grants, wills, written agreements or other causes justified by laws and regulations. In addition, Copyright has qualified as an object of fiduciary guarantee, among others. It belongs to the category of things and has economic value, so Copyright allows it to be used as an object of debt guarantee. The Copyright that will be used as the object of debt guarantee must be registered in the general register of works as proof of ownership of a Copyright. However, in its laws, Copyright does not have to be registered. Another condition is that the validity period of copyright protection has not expired, this is important in terms of the economic value of the Copyright because it can still be maintained against anyone.